2021
DOI: 10.1021/acssuschemeng.1c02442
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Lithium Extraction from Brine with a High Sodium Content by Adsorption-Coupled Electrochemical Technology

Abstract: The demand for lithium resources continues to increase due to the rapid development of electronic vehicles, energy storage equipment, and other electronic products. Extracting lithium from salt lake brines is of great significance because of the predominance of brine lithium resources. Because both sodium and lithium ions are monovalent cations and have similar chemical properties, it is difficult to extract lithium from high-sodium brine. Herein, an adsorption-coupled electrochemical (ACEC) technology was uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…4f). When data are reported, the average number of cycles is fewer than 10 (that is, <100 h) 83,[131][132][133][134][135] . For the different LiMn 2 O 4 -based ion exchange systems, Li + adsorption capacity is reduced by 17.2% after 50 cycles 136 , 2.5% after 5 cycles 52 and 43% after 30 cycles 137 , pointing to the importance of medium-term to long-term stability tests.…”
Section: Scaling-up Requirements and Potentialmentioning
confidence: 99%
“…4f). When data are reported, the average number of cycles is fewer than 10 (that is, <100 h) 83,[131][132][133][134][135] . For the different LiMn 2 O 4 -based ion exchange systems, Li + adsorption capacity is reduced by 17.2% after 50 cycles 136 , 2.5% after 5 cycles 52 and 43% after 30 cycles 137 , pointing to the importance of medium-term to long-term stability tests.…”
Section: Scaling-up Requirements and Potentialmentioning
confidence: 99%
“…More recently, in 2021, another MCDI cell was assembled using LMO as the positive electrode, and an AC electrode cover with an anion exchange membrane. [292] Studying this device, Su et al reported 51.8 mg Li g −1 of lithium recovered when treating a brine with a high Na content (675 mg Li+ L −1 Na/Li ratio = 48.6), thanks to the use of carbon-coated manganese oxide.…”
Section: Membrane-cdi Systemsmentioning
confidence: 99%
“…Currently, a variety of methods for Li + extraction from salt lakes have been developed, including lime-soda evaporation, ion exchange, solvent extraction, adsorption, membrane method, and electrochemical extraction. Lime-soda evaporation has been used in mass production; however, this method suffers from some major issues, e.g., low efficiency, high energy consumption, and long time consumption. , Ion exchange has high selectivity for Li + ; however, this method raises environmental concerns owing to the acid wash procedure for regeneration of ion-exchange absorbents. Solvent extraction is suitable for treating brine with a high magnesium–lithium ratio; however, plenty of organic solvents are used in this process, causing environmental pollution. , Ion-sieve adsorption presents excellent selectivity for Li ions; however, this method still has some drawbacks, such as the risk of environmental pollution, slow adsorption rates, and poor recyclability. Membrane separation is a pure physical separation operation.…”
Section: Introductionmentioning
confidence: 99%